Chest pain in Brugada syndrome: Prevalence, correlations, and prognosis role. Issue 4 (26th February 2020) - Sebai, Fatiha; Rollin, Anne; Mondoly, Pierre; Voglimacci‐Stephanopoli, Quentin; Dupin‐Deguine, Delphine; Bieth, Eric; Hocini, Meleze; Monteil, Benjamin; Mandel, Franck; Galinier, Michel; Carrié, Didier; Haïssaguerre, Michel; et al.
Abstract: Background: Brugada syndrome (BrS) is sometimes diagnosed because of chest pain. Prevalence and characteristics of such BrS patients are unknown. Methods: A total of 200 BrS probands were retrospectively included. BrS diagnosis made because of chest pain (n = 34, 17%) was compared to the other ones. Results: BrS probands with diagnosis because of chest pain had significantly more often smoker habits, increased body mass index, and familial history of coronary artery disease but less frequently previous resuscitated sudden death/syncope or atrial fibrillation. Presence of coronary spasm and familial coronary artery disease were independently associated with BrS diagnosed because of chest pain. They presented more often with spontaneous type 1 ST elevation (59% vs 26%, P  = .0004) and higher ST elevation during the episode of chest pain compared to other patients or compared to baseline electrocardiogram after chest pain resumption. ST elevation during chest pain was lower compared to ajmaline test. A total of 20% of them had significant coronary artery disease and four (11%) had coronary spasm, and they experienced more often recurrent chest pain episodes (24% vs 5%, P  = .0002). Presence of chest pain at BrS diagnosis was not correlated to future arrhythmic events in univariate analysis. Only previous sudden cardiac death (SD)/syncope and familial SD were still significantly associated with outcome in multivariate analysis. Conclusion: Chest pain is a common cause for BrS diagnosis, although major part is not apparently explained by ischemic heart disease. Mechanisms leading to chest main remain unknown in the other ones. ST elevation is higher in this situation but does not seem to carry poor prognosis.